Transcriptome Analysis of the Inhibitory Effect of Sennoside A on the Metastasis of Hepatocellular Carcinoma Cells - Le, Jiamei; Fu, Yi; Han, Qiuqin; Ma, Yujie; Ji, Houlin; Wei, Xindong; Chen, Yifan; Sun, Yongning; Gao, Yueqiu; Wu, Hailong (Frontiers in Pharmacology, 2021)
Sennoside A (SA) is a bioactive component of Rheum officinale Baill. with an activity of irritant laxative, which has been reported to possess therapeutic potential in various diseases or conditions including obesity, insulin resistance, liver steatosis, prostate cancer and pancreatic cancer progression. However, whether SA has therapeutic potential in hepatocellular carcinoma (HCC) treatment remains elusive. In this study, we treated two HCC cell lines, HepG2 and SMMC-7721 with SA and found that SA selectively inhibited the growth of HCC cells by proliferation assay. SA has a good inhibitory effect on proliferation of HepG2 cells in a concentration dependent manner, but there was no effect on SMMC-7721 cells. Then we conducted transwell assays and transcriptome analysis in HCC cells and examined the effects of SA on HCC in vivo. The results showed that SA significantly inhibited the migration and invasion of HCC. Comparison of RNA-seq transcriptome profiles from control groups and SA-treated groups identified 171 and 264 differentially expressed genes (DEGs) in HepG2 and SMMC-7721 cells respectively, in which includes 2 overlapping up-regulated DEGs and 12 overlapping down-regulated DEGs between HepG2 and SMMC-7721 cells. The qPCR were applied to investigate the transcriptional level of 9 overlapping down-regulated DEGs related to cancer metastasis, and the results were consistent with RNA-seq data. The dominate pathways including Wnt signaling pathway, TNF signaling pathway, VEGF signaling pathway, and NF-κB signaling pathway were strongly inhibited by SA, which are involved in regulating cancer metastasis. Finnaly, we confirmed that the downregulation of KRT7 and KRT81 could inhibit HCC metastasis. This study has provided new insight into the understanding of the inhibitory effects and potential targets of SA on the metastasis of HCC.